Researching References on Interpretation of Personal Data in the Indonesian Constitution - Faiz Rahman; Dian Agung Wicaksono (Jurnal Penelitian Hukum De Jure, 2021)
The discourse on personal data protection has been developed for a long time, even before the advent of internet technology. In the Indonesian context, issues relating to the personal data protection have begun to develop in recent years, responding to the increasingly rapid development of digital technology. Currently the Personal Data Protection Bill is again included in the 2021 Priority National Legislation Program in response to the importance of regulations relating to personal data protection in Indonesia. The fundamental thing that often escapes the discourse on the personal data protection in Indonesia is related to how personal data is positioned in a constitutional perspective based on the 1945 Constitution of the Republic of Indonesia if personal data is considered as something that must be protected. This research specifically answered the questions: (a) how is the conceptual interpretation of personal data? (b) how is personal data positioned in the perspective of the Indonesian constitution? This research is a normative juridical research, conducted by analyzing secondary data obtained through literature review. The results of this research indicated that the conceptual interpretation of personal data is still a growing discourse. As for personal data in the perspective of the Indonesian constitution, it can be seen by looking at the legal-historical aspect in the discussion of the amendments to the 1945 Constitution, especially in Article 28G paragraph (1) of the 1945 Constitution of the Republic of Indonesia which is hypothesized as a reference for personal data protection.